Islamic Schools As A Means Of Millenial Generation’s Education - Handayani, Titik; Saadah, Lailatis (State Islamic Institute of Madura, 2019)
Islamic schools are expected to be a means to achieve the goals of Islamic education. Therefore, they should not focus on religion field only, but they should be balanced by science. It is because of the goals of Islamic education guide us to achieve the happiness of the world and here after. So that, Islamic schools should be able to facilitate millennial generation by Islamic religion and science in order to produce the graduates who are knowledgeable and having good character. In addition, they are also expected to produce the competitive graduates. Therefore, this paper will discuss about the goals of Islamic education, and how the Islamic schools, focusing on madrasah should design their curriculum for millennial generation to achieve the goals of Islamic education. Correlating of this statement, Curriculum for MI and MTS should focus on transferring knowledge and forming character, whereas, curriculum for MA should focus on life skill training besides both of those competencies. Nevertheless, the implementation of curriculum will be achieved maximal when it is supported by headmaster who will be able to manage their human resources. So that, madrasah will be a means of millennial generation’s education. Keyword: Islamic education, Islamic schools, millennial generation, Islamic schools for millennial generation